Loss of tumor suppressor miR-126 contributes to the development of hepatitis B virus–related hepatocellular carcinoma metastasis through the upregulation of ADAM9 - Le-yang Xiang; Huo-hui Ou; Xin-cheng Liu; Zhan-jun Chen; Xiang-hong Li; Yu Huang; Ding-hua Yang (Tumor Biology)
Hepatocellular carcinoma is the most common histological type of primary liver cancer, which represents the second leading cause of cancer-related mortality. MiR-126 was reported to be downregulated in hepatocellular carcinoma tissues, compared with its levels in noncancerous tissues. However, baseline miR-126 expression levels in hepatitis B virus–related hepatocellular carcinoma patients who did not undergo pre-operational treatment remains unknown since hepatitis B virus infection and pre-operational transcatheter arterial chemoembolization were shown to upregulate miR-126 expression. Here, we demonstrated that miR-126 is generally downregulated in a homogeneous population of pre-operational treatment–naïve hepatitis B virus–related hepatocellular carcinoma patients (84.0%, 84/100), and its expression is significantly associated with pre-operational alpha-fetoprotein levels ( p  < 0.05), microvascular invasion ( p  < 0.05), tumor metastasis ( p  < 0.05), as well as early recurrence (12 months after surgery; p  < 0.01). Furthermore, the results of our study revealed that miR-126 is negatively correlated with ADAM9 expression in hepatitis B virus–related hepatocellular carcinoma patients. Overexpression of miR-126 was shown to attenuate ADAM9 expression in hepatocellular carcinoma cells, which subsequently inhibits cell migration and invasion in vitro. In addition, Cox proportional hazards regression model analysis showed that ADAM9 levels, tumor number, microvascular invasion, and tumor metastasis rate represent independent prognostic factors for shorter recurrence-free survival. In conclusion, we demonstrated that the loss of tumor suppressor miR-126 in hepatitis B virus–related hepatocellular carcinoma cells contributes to the development of metastases through the upregulated expression of its target gene, ADAM9. MiR-126-ADAM9 pathway–based therapeutic targeting may represent a novel approach for the inhibition of hepatitis B virus–related hepatocellular carcinoma metastases.